2018
DOI: 10.1369/0022155418814231
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Algorithm to Quantify Collagen Distribution in Aortic Wall

Abstract: Arterial diseases including abdominal aortic aneurysm and atherosclerosis are biomechanical diseases characterized by significant changes in the structure and strength of the vessel wall. It is now established that local variations in fibrillar collagen and elastin matrix turnover is critical to arterial stiffening and progression of the disease. The collagen content in the aortic wall has nominally been quantified by biochemical assays and immunohistochemical analysis as the total amount because of the diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Collagen content was quantified as the area of red of each image. The green channel of RGB images from picrosirius-red-stained lung sections was binarized with MATLAB software as previously reported 50 to quantify the infiltrates. Black pixels were counted, and the density was shown as pixel count per image.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen content was quantified as the area of red of each image. The green channel of RGB images from picrosirius-red-stained lung sections was binarized with MATLAB software as previously reported 50 to quantify the infiltrates. Black pixels were counted, and the density was shown as pixel count per image.…”
Section: Methodsmentioning
confidence: 99%
“…Collagens actively participate in arterial wall remodeling during atherogenesis. It is well-studied and documented in the literature that local variations in fibrillar collagen are critical to arterial stiffening and the progression of AS ( 26 ). In our study, the increasing and redistribution of COL I and COL III were observed in the human carotid AS tissue.…”
Section: Discussionmentioning
confidence: 99%
“…(B) COL I, COL III, VCAM-1, ICAM-1, and p-JNK protein expression was determined by Western blot in the CAVSMCs treated with SP600125 (*p < 0.05 and **p < 0.01 vs. control group, # p < 0.05, ## p < 0.01, and ### p < 0.001 si-PRDX2+SP group, && p < 0.01, &&& p < 0.001, and &&&& p < 0.0001 vs. si-PRDX2-NC+SP group). (C) COL I, COL III, VCAM-1, ICAM-1, and p-ERK protein expression was determined by Western blot in the CAVSMCs treated with PD98059 (*p < 0.05 and **p < 0.01 vs. control group, # p < 0.05, ## p < 0.01, and ### p < 0.001 vs. si-PRDX2+PD group, && p < 0.01, &&& p < 0.001, and &&&& p < 0.0001 vs. si-PRDX2-NC+PD group).AS(26). In our study, the increasing and redistribution of COL I and COL III were observed in the human carotid AS tissue.…”
mentioning
confidence: 93%
“…Total collagen content of PSR stained sections was quantified by an elaborated analysis protocol using MatLab as described before [8]. PSR stained sections were imaged by a Leica microscope (Leica DM 4000B, Leica Biosystems Inc., USA) and a polarized filter (Leica ICT/Pol, Leica Biosystems Inc; Fig.…”
Section: Collagen Quantificationmentioning
confidence: 99%
“…The results obtained are compared to histological analyses and automated collagen quantification as described previously [8].…”
Section: Introductionmentioning
confidence: 99%